The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1677/joe-07-0517
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic and tissue-specific expression of preproghrelin in the Atlantic halibut, Hippoglossus hippoglossus L.

Abstract: Ghrelin is a conserved vertebrate hormone that affects both GH release and appetite. We have cloned and characterized Atlantic halibut preproghrelin cDNA and examined for the first time preproghrelin expression during fish larval development using quantitative real-time PCR. In addition, cellular sites of expression in larvae and tissue-specific expression in 3-year-old halibut were studied. A full-length cDNA for preproghrelin was isolated from halibut stomach tissue. The 899 bp cDNA encodes an open reading f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 38 publications
3
22
0
1
Order By: Relevance
“…Since the mRNA tissue distribution of Ghsr1b is much wider than Ghsr1a in grouper, we speculate that GHSR1b may mediate some unknown functions independent of ghrelin/GHSR1a system. During embryonic and larval development, gpGhsr1a mRNA was expressed from the neurula stage on, coinciding with the development of the nervous system and prior to the appearance of its ligand, ghrelin, which is expressed from hatching in Atlantic halibut (Manning et al 2008). The expression of gpGhsr1b mRNA can be detected as of the blastula stage, even earlier than gpGhsr1a.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since the mRNA tissue distribution of Ghsr1b is much wider than Ghsr1a in grouper, we speculate that GHSR1b may mediate some unknown functions independent of ghrelin/GHSR1a system. During embryonic and larval development, gpGhsr1a mRNA was expressed from the neurula stage on, coinciding with the development of the nervous system and prior to the appearance of its ligand, ghrelin, which is expressed from hatching in Atlantic halibut (Manning et al 2008). The expression of gpGhsr1b mRNA can be detected as of the blastula stage, even earlier than gpGhsr1a.…”
Section: Discussionmentioning
confidence: 98%
“…The existence of ghrelin has now been demonstrated in nine teleostean species (reviewed by Unniappan & Peter 2005, Kaiya et al 2008: goldfish, Carassius auratus (Unniappan et al 2002); Japanese eel, Anguilla japonica (Kaiya et al 2003a); rainbow trout, Oncorhynchus mykiss (Kaiya et al 2003b); two tilapia species, Oreochromis mossambicus (Kaiya et al 2003c) and Oreochromis niloticus (Parhar et al 2003); channel catfish, Ictalurus punctatus ; black sea bream, Acanthopagrus schlegeli (Yeung et al 2006); sea bass, Dicentrarchus labrax (Terova et al 2008); and Atlantic halibut, Hippoglossus hippoglossus L. (Manning et al 2008). Physiological roles of ghrelin in teleosts have also been widely studied, including effects on GH secretion (Riley et al 2002, Kaiya et al 2003a,b,c, Ran et al 2004, Shepherd et al 2007, appetite stimulation (Unniappan et al 2002, Matsuda et al 2006a, Jönsson et al 2007, Miura et al 2007, Shepherd et al 2007, water intake (Kozaka & Ando 2003), reproduction (Mustonen et al 2002, Parhar et al 2003, immunity (Yada et al 2006), growth (Riley et al 2005, Fox et al 2007, intestinal motility (Olsson et al 2008), and locomotor behavior (Matsuda et al 2006a,b).…”
Section: Introductionmentioning
confidence: 99%
“…5,[12][13][14] So far, ghrelin has been identified in various fishes. [15][16][17][18][19][20][21][22] As in mammals, [23][24][25][26][27] ghrelin increases food intake and promotes body weight gain in fishes. 18,[28][29][30][31][32] Similar to mammals, 23,24 it was demonstrated that endogenous ghrelin levels and ghrelin-induced food intake depend on nutrient/feeding status.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, in the latter, ghrelin peptide was recently identified in two elasmobranchs, such as hammerhead shark and blacktip reef shark (Kawakoshi et al, 2007), and in some teleost species like goldfish (Unniappan et al, 2002), Nile tilapia (Parhar et al, 2003), rainbow trout , sea bass (Terova et al, 2008), zebrafish (Amole and Unniappan, 2008), and Atlantic halibut (Manning et al, 2008).…”
Section: Introductionmentioning
confidence: 99%